Preparation, characterization and electrochemical studies of dinuclear copper(II) complexes with pseudohalides and bidentate amines on platinum electrode in acetonitrile - Sargentelli, V. [UNESP]; Benedetti, Assis Vicente [UNESP]; Mauro, Antonio Eduardo [UNESP] (FapUNIFESP (SciELO), 1997)
The complexes: [Cu(N 3) 2(N,N-diEten)] 2, [Cu(N 3) 2(tmeen)] 2, [Cu(N 3)(NCO)(N,N-diEten)] 2, [Cu(N 3) 2(N,N′-diMeen)] 2 and [Cu(N 3)(NCO)(tmeen)] 2 were prepared, characterized and their electrochemical behavior was investigated by cyclic voltammetry and controlled potential electrolysis. Cyclic voltammograms for all complexes studied are similar and exhibit one pair of current peaks in the range of -0.65 to +0.0 V. The number of electrons obtained from controlled potential electrolysis at ca. -0.55 V for all compounds was 1.8 ≤ n ≤ 2.1, indicating that both copper(II) metallic centres in the molecule were reduced to copper (I). Comparing the peak potential values for these complexes one can observe that the redox process corresponding to copper(II)/copper(I) couple is slightly influenced by the σ-basicity of the ligands. © 1997 Soc. Bras. Química.
Keywords: Copper complexes; Cyclic voltammetry of copper complexes; N′; N′-dialkyldiamine ligands; Pseudohalyde ligands